Endoplasmic reticulum generates calcium signalling microdomains around the nucleus and spindle in syncytial Drosophila embryos. (22nd May 2006) - Parry, H.; McDougall, A.; Whitaker, M.
Abstract : Cell cycle calcium signals are generated by inositol trisphosphate-mediated release of calcium from internal stores [Ciapa, Pesando, Wilding and Whitaker (1994) Nature (London) 368, 875–878; Groigno and Whitaker (1998) Cell 92, 193–204]. The major internal calcium store is the ER (endoplasmic reticulum): the spatial organization of the ER during mitosis is important in defining a microdomain around the nucleus and mitotic spindle in early Drosophila embryos [Parry, McDougall and Whitaker (2005) J. Cell Biol. 171, 47–59]. Nuclear divisions in syncytial Drosophila embryos are accompanied by both cortical and nuclear localized calcium transients. Mitosis is prevented by the Ins P 3 antagonists Xestospongin C and heparin. Nuclear-localized transients and cortical transients rely on extraembryonic calcium, suggesting that ER calcium levels are maintained by calcium influx.